IEM/ICE Conference on Solid and Industrial Wastes Management Systems : [papers] - IEM/ICE Conference on Solid and Industrial Wastes Management Systems (1994 : Kuala Lumpur); Institution of Engineers (Malaysia); Institution of Civil Engineers (Great Britain) (Kuala Lumpur : IEM, 1994)
10